Lithium silicate-based mixed-phase material and all-solid-state battery
Patent Information
- Application Number
- JP2023139610
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-30
- Publication Date
- 2025-03-13
AI Technical Summary
【0011】 本発明によれば、分解電圧が高い新たな固体電解質が実現できた。その固体電解質を例えば正極活物質の保護材として用いることによって、全固体リチウムイオン二次電池の充電電圧を向上させることが可能になる。
Smart Images

Figure 2025033701000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a lithium silicate-based multiphase material having lithium ion conductivity, and also to an all-solid-state battery using the lithium silicate-based multiphase material. In this specification, the term "all-solid-state battery" refers to a type of battery that has a structure in which an ionically conductive solid material is disposed between a conductive material on the positive electrode side and a conductive material on the negative electrode side, and does not use an electrolyte. All-solid-state lithium-ion secondary batteries are included in the above all-solid-state batteries. The positive electrode active material is included in the "conductive material on the positive electrode side". The negative electrode active material is included in the "conductive material on the negative electrode side". [Background technology]
[0002] In all-solid-state lithium-ion secondary batteries, a solid electrolyte that functions as a separator is placed between the positive and negative active materials, and lithium ions are conducted between the two active materials via the solid electrolyte. Various solid electrolytes, such as sulfide-based, oxide-based, and polymer-based, have been developed, but sulfide-based electrolytes are considered to be advantageous at present in terms of ion conductivity and manufacturing costs.
[0003] In all-solid-state lithium-ion secondary batteries, there is a problem that the interfacial resistance between the positive electrode active material and the solid electrolyte, which is the separator, increases, and the performance such as the battery capacity is easily reduced. This increase in interfacial resistance is mainly due to the reaction between the positive electrode active material and the solid electrolyte, which forms a high resistance site on the surface of the positive electrode active material, and is likely to be a problem when a sulfide-based solid electrolyte is used as the separator. Therefore, attempts have been made to cover the surface of the positive electrode active material with a lithium ion conductive oxide (LiNbO3 is a well-known representative) or a solid electrolyte made of a halide, which functions as a protective material, to prevent the positive electrode active material from reacting with the solid electrolyte, which is the separator. However, the solid electrolyte used as a protective material deteriorates when a high charging voltage is applied. In the case of LiNbO3, a representative protective material, the deterioration progresses rapidly when the charging voltage exceeds 4.45V.
[0004] Patent Document 1 describes the use of a halide containing Cl as a solid electrolyte that covers at least a part of the surface of the positive electrode active material. In the examples of Patent Document 1, an evaluation experiment was conducted using an electrochemical cell in which a halide solid electrolyte was placed in contact with a sulfide-based solid electrolyte. According to the experiment, it was evaluated that the halide solid electrolyte reacted and oxidized and decomposed at a voltage of 3.88 to 4.47 V vs. In-Li at room temperature (Table 1). Since this measured value is converted to a value based on metallic Li and is a value that is 0.6 V higher (paragraph 0173), it can be seen that the oxidation resistance during charging of the coating solid electrolyte (halide containing Cl) according to the technology of Patent Document 1 was raised to about 4.48 to 5.07 V, which is higher than 4.45 V. However, in the above experiment, the voltage at which a current value of 3 μA or more begins to flow is defined as the oxidative decomposition voltage and evaluated (paragraph 0175, Figure 3).
[0005] On the other hand, lithium silicate-based compounds doped with transition elements such as Fe are known as substances that are considered to be applicable to positive electrode active materials (for example, Patent Document 2, paragraph 0005). However, no lithium silicate-based substance that exhibits excellent deterioration resistance and is useful as a protective material for protecting positive electrode active materials from sulfide-based solid electrolytes in all-solid-state batteries is known. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] International Publication No. 2020 / 174868 [Patent Document 2] International Publication No. 2010 / 089931 Summary of the Invention [Problem to be solved by the invention]
[0007] From the viewpoint of energy density, the higher the charging voltage of a battery, the better. Therefore, there is a demand for a solid electrolyte that has sufficient lithium ion conductivity and can increase the charging voltage. However, since increasing the charging voltage deteriorates the solid electrolyte as a protective material, it has generally not been easy to increase the charging voltage above 4.45V in the past. Although it is considered possible to achieve a charging voltage exceeding 4.45V in an all-solid-state battery according to the technology of Patent Document 1, there is a demand for the establishment of a technology that can achieve an even higher charging voltage in the future.
[0008] The present invention aims to provide a technique that is advantageous for ensuring sufficient lithium ion conductivity and further improving the charging voltage in all-solid-state batteries such as all-solid-state lithium ion secondary batteries. [Means for solving the problem]
[0009] In order to achieve the above object, the present specification discloses the following invention. [1] An ionically conductive lithium silicate-based mixed-phase material in which the presence of four phases, Li4SiO4, Li2SiO3, Li2CO3, and LiOH H2O, is observed in the X-ray diffraction pattern using CuKα radiation. [2] The lithium silicate-based mixed phase material according to [1] above, having a Li / Si molar ratio in the range of 3.5 to 4.5. [3] The lithium silicate-based mixed phase material according to the above [1] or [2], wherein the I1 / I0 ratio is 0.05 or more, where I0 is the diffraction peak intensity of the Li4SiO4 crystal (-1 1 0) plane and I1 is the diffraction peak intensity of the LiOH·H2O crystal (-3 3 1) plane in the X-ray diffraction pattern. [4] The lithium silicate-based mixed phase material according to the above [1] or [2], wherein the diffraction peak intensity of the Li4SiO4 crystal (-1 1 0) plane in the X-ray diffraction pattern is I0 and the diffraction peak intensity of the LiOH·H2O crystal (-3 3 1) plane is I1, the I1 / I0 ratio is 0.25 or more. [5] An all-solid-state battery comprising the ion-conductive lithium silicate-based mixed phase material according to any one of [1] to [4] above between a conductive material on a positive electrode side and a conductive material on a negative electrode side. [6] An all-solid-state battery comprising an ion-conductive lithium silicate-based mixed-phase material according to any one of [1] to [4] above and a solid electrolyte containing a sulfide as a main component between a conductive material on a positive electrode side and a conductive material on a negative electrode side. [7] An all-solid-state battery including a positive electrode active material, a first solid electrolyte made of the ion-conductive lithium silicate-based mixed phase material according to any one of the above [1] to [4], a second solid electrolyte containing a sulfide as a main component, and a negative electrode active material, wherein the first solid electrolyte is interposed between the positive electrode active material and the second solid electrolyte, thereby preventing direct contact between the positive electrode active material and the second solid electrolyte. [8] An all-solid-state battery comprising: particles of a positive electrode active material coated with a first solid electrolyte made of the ion-conductive lithium silicate-based mixed phase material according to any one of the above [1] to [4]; a second solid electrolyte containing a sulfide as a main component; and a negative electrode active material. [9] A method for producing an ion-conductive lithium silicate-based mixed phase material according to any one of the above [1] to [4], comprising a step of dry-grinding lithium silicate Li4SiO4 in an air atmosphere having a dew point temperature of -30°C or higher.
[10] A step of producing a lithium silicate-based mixed phase material by dry grinding lithium silicate Li4SiO4 in an air atmosphere having a dew point temperature of -30°C or higher; Heat-treating the lithium silicate-based mixed phase material in air at 100° C. or more and 500° C. or less; The method for producing an ion-conductive lithium silicate-based mixed phase material according to any one of the above [1] to [4],
[0010] In this specification, the term "lithium silicate-based mixed phase material" refers to a Li- and Si-containing material in which a lithium silicate Li4SiO4 phase and other Li compound phases coexist. "Ionic conductivity" refers to a value of 1.0×10 -11 This refers to the property of exhibiting ionic conductivity of 100 S / cm or more. Effect of the Invention
[0011] According to the present invention, a new solid electrolyte with a high decomposition voltage has been realized. By using the solid electrolyte as a protective material for a positive electrode active material, it becomes possible to improve the charging voltage of an all-solid-state lithium ion secondary battery. [Brief description of the drawings]
[0012] [Figure 1] 1 is an X-ray diffraction pattern using CuKα radiation for the test material (lithium silicate-based mixed phase material) obtained in Example 2. [Diagram 2] FIG. 1 is a schematic diagram illustrating a cross-sectional structure of one embodiment of an all-solid-state battery using a first solid electrolyte made of the above-mentioned lithium silicate-based mixed phase material according to the present invention and a second solid electrolyte containing a sulfide as a main component. [Diagram 3] FIG. 1 is a schematic diagram illustrating a cross-sectional structure of one embodiment of an all-solid-state battery using particles of a positive electrode active material coated with a first solid electrolyte made of the above-mentioned ion-conductive lithium silicate-based mixed phase material according to the present invention, and a second solid electrolyte containing a sulfide as a main component. [Figure 4] FIG. 2 is a cross-sectional view showing a schematic stacked structure of an electrochemical cell produced for evaluating high voltage application resistance characteristics (decomposition voltage) in the examples. [Diagram 5] 5 is a graph illustrating a potential-current curve measured using the electrochemical cell of FIG. 4. [Figure 6] 1 is an X-ray diffraction pattern using CuKα radiation for the test material obtained in Comparative Example 1. [Figure 7] 4 shows an X-ray diffraction pattern using CuKα radiation for the Li4SiO4 powder (before being subjected to dry grinding) used as the raw material in each example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] [Lithium silicate-based mixed phase material] According to the research of the inventors, it has been found that a lithium silicate-based mixed phase material, in which the presence of four phases Li4SiO4, Li2SiO3, Li2CO3, and LiOH·H2O is observed in an X-ray diffraction pattern using CuKα radiation, has ion conductivity and exhibits a high decomposition voltage exceeding 4.45 V. This lithium silicate-based mixed phase material can be synthesized using lithium silicate Li4SiO4 as a raw material, as described below. The Li / Si molar ratio range of this lithium silicate-based mixed phase material can be, for example, a range in the vicinity of the Li / Si molar ratio of the raw material of 4.0, specifically, a range of 3.5 to 4.5.
[0014] Figure 1 shows an example of an X-ray diffraction pattern using CuKα radiation for the lithium silicate mixed phase material obtained in Example 2 described later. The positions (diffraction angles) of the X-ray diffraction peaks using CuKα radiation for Li4SiO4, Li2SiO3, Li2CO3, and LiOH·H2O are shown in the following ICDD card. (ICDD card number) Li4SiO4:00-037-1472 Li2SiO3:01-070-0330 Li2CO3:00-022-1141 LiOH·H2O:01-076-1073 In FIG. 1, the diffraction peaks of these four compound phases are observed.
[0015] In order to specify the peak intensity ratio of the above four types of compound phases, the following diffraction peaks that do not overlap with each other can be used. Li4SiO4: (-1 1 0) plane, 2θ=22.3°±0.5° Li2SiO3: (1 1 1) plane, 2θ=27.3°±0.5° Li2CO3: (-1 1 0) plane, 2θ=21.5°±0.5° LiOH·H2O: (-3 3 1) plane, 2θ=52.6°±0.5° Here, the diffraction peak intensity of a certain diffraction peak means the peak height expressed by the X-ray count value (cps) at the apex of the diffraction peak. In the lithium silicate mixed phase material of the present invention, in the peak intensities using the above diffraction peaks, the ratios of the peak intensities of Li2SiO3, Li2CO3 and LiOH·H2O to the peak intensity of Li4SiO4 are all 0.01 or more.
[0016] According to the study by the inventors, when the diffraction peak intensity of the Li4SiO4 crystal (-1 1 0) plane is I0 and the diffraction peak intensity of the LiOH·H2O crystal (-3 3 1) plane is I1, it was found that a lithium silicate-based mixed phase material with an I1 / I0 ratio of 0.05 or more exhibits sufficient ionic conductivity, and the ionic conductivity is greatly improved when the I1 / I0 ratio is 0.25 or more. Therefore, when ionic conductivity is important, it is effective to control the I1 / I0 ratio to 0.25 or more. The I1 / I0 ratio is not particularly limited as long as it improves ionic conductivity, but it may be controlled to, for example, a range of 0.70 or less.
[0017] [Method for producing lithium silicate-based mixed-phase materials] The above-mentioned ion-conductive lithium silicate-based mixed phase material can be synthesized by dry grinding lithium silicate Li4SiO4 in an air atmosphere with a dew point temperature of -30°C or higher. It was confirmed that when Li4SiO4 powder is mechanically ground in the above atmosphere, the Li4SiO4 particles are broken down while reacting with carbon dioxide CO2 and water H2O in the air, resulting in a powder containing four phases of Li4SiO4, Li2SiO3, Li2CO3, and LiOH·H2O, that is, a lithium silicate-based mixed phase material. It was found that the lithium silicate-based mixed phase material generated by applying a certain degree of grinding operation exhibits ion conductivity and has a high decomposition voltage. Since there is little water in an air atmosphere with a dew point temperature lower than -30°C, it is difficult to obtain an ion-conductive lithium silicate-based mixed phase material in which the above four phases coexist. There is no particular limit to the upper limit of the dew point temperature, but for example, an air atmosphere with a dew point temperature of 30°C or lower or 20°C or lower is easily applicable. The dew point temperature can be measured by a general dew point meter such as a capacitance type, a mirror cooling type, etc. Dry grinding can be performed by using a general grinding device such as a ball mill.
[0018] Furthermore, the lithium silicate-based mixed-phase material produced by the above-mentioned dry grinding can be subjected to a heat treatment in the atmosphere at 500°C or less. This heat treatment further advances the reaction between the powder and carbon dioxide in the atmosphere, and the ratio of Li2CO3 in the mixed-phase material can be increased. This can improve the decomposition voltage compared to before the heat treatment. It is effective to set the heating temperature to 100°C or more. In order to further improve the decomposition voltage, it is preferable to set the heating temperature to 150°C or more and 300°C or less. Note that if the heating temperature exceeds 500°C, the lithium silicate-based mixed-phase material is likely to become a Li4SiO4 single-phase material, making it difficult to maintain the state exhibiting ionic conductivity.
[0019] When lithium silicate Li4SiO4 is used as the raw material, the peak intensity ratio I1 / I0 of the LiOH·H2O phase and Li4SiO4 phase mentioned above can be controlled by adjusting the dry-milling time and the temperature of the subsequent heat treatment, making it possible to optimize the balance between ionic conductivity and decomposition voltage depending on the application.
[0020] [All-solid battery] The lithium silicate-based mixed-phase material according to the present invention has lithium ion conductivity, and can therefore be used as a solid electrolyte, which is a component of an all-solid-state lithium ion secondary battery. Since this lithium silicate-based mixed-phase material has a high decomposition voltage, it is useful as a protective material for protecting a positive electrode active material from reactions with a sulfide-based solid electrolyte, and for example, by replacing LiNbO3, a conventionally widely used protective material, with the lithium silicate-based mixed-phase material according to the present invention, an effect of improving the charging voltage can be obtained. As an arrangement structure of such an all-solid-state battery, an arrangement structure having the above-mentioned ion-conductive lithium silicate-based mixed-phase material according to the present invention and a solid electrolyte mainly composed of sulfide between a conductive material on the positive electrode side and a conductive material on the negative electrode side can be mentioned.
[0021] FIG. 2 shows a schematic cross-sectional structure of one embodiment of an all-solid-state battery using the first solid electrolyte made of the lithium silicate-based mixed phase material according to the present invention and the second solid electrolyte mainly composed of sulfide. In this figure, the cell structure is extremely simplified in order to explain the positional relationship of each member. The conductive material 3 on the positive electrode side and the conductive material 4 on the negative electrode side face each other with the first solid electrolyte 1 and the second solid electrolyte 2, which is a separator, sandwiched between them. The first solid electrolyte 1 is interposed between the conductive material 3 on the positive electrode side and the second solid electrolyte 2. There is a contact portion between the conductive material 3 on the positive electrode side and the first solid electrolyte 1, and there is also a contact portion between the first solid electrolyte 1 and the second solid electrolyte 2.
[0022] In an all-solid-state battery, the conductive material 3 on the positive electrode side is usually composed of a positive electrode active material 31 and a conductive material 32 other than the positive electrode active material. The positive electrode active material 31 is an ion conductive material and a conductive material. The conductive material 32 other than the positive electrode active material is a current collector, a conductive assistant, etc. In an actual all-solid-state battery, the positive electrode material is generally composed of conductive members such as a current collector, a large number of particles of a positive electrode active material, a large number of particles of a conductive assistant, and particles of an ion conductive material (solid electrolyte) mixed to fill the gaps between the particles of the positive electrode active material. The conductive material 3 on the positive electrode side in FIG. 2 is a schematic diagram showing the positional relationship of the part of such a positive electrode material composed of a conductive member to the first solid electrolyte 1, and one particle of the positive electrode active material 31 is shown as a representative.
[0023] Known substances can be used as the positive electrode active material 31, and new positive electrode active materials may also be developed and applied. Representative known positive electrode active materials include LiCoO2 (LCO type), LiNiO2 (LNO type), LiMn2O4 (LMO type), LiNiCoAlO2 (NCA type), LiNiCoMnO2 (NCM type), Li2MnO3-LiNiCoMnO2 (solid solution type), LiNiMnO4 (spinel type), LiMnFePO4 (phosphate type), Li2FeSiO4 (silicate type), and the like.
[0024] The first solid electrolyte 1 is made of the lithium silicate-based mixed phase material according to the present invention described above. The second solid electrolyte 2 is composed mainly of sulfide and functions as a separator. "Composed mainly of sulfide" means that the total content of sulfide in the constituent materials of the second solid electrolyte 2 is 50 mass% or more. One type of sulfide may be used alone, or two or more types of sulfides may be used in combination.
[0025] The above sulfides can be any known substance with ionic conductivity, and new ionic conductive substances may also be developed. Representative known ionic conductive substances include Li6PS5Cl (crystal (argyrodite)), Li 9.54 S 1.74 P 1.44 S 11.7 Cl 0.3 (crystal), Li 10 GeP2S 12 (crystal), 30Li2S 26B2S3 44LiI (glass), 63Li2S 36SiS2 1Li3PO4 (glass), 57Li2S 38SiS2 5Li4SiO4 (glass), 70Li2S 30P2S5 (glass), Li7P3S 11 (glass ceramic), Li 3.25 P 0.95 S4 (glass ceramic) and others.
[0026] In the embodiment of FIG. 2, a first solid electrolyte 1 (lithium silicate-based mixed phase material) is interposed between a positive electrode active material 31 and a second solid electrolyte 2 (containing a sulfide as a main component), thereby providing a structure in which direct contact between the positive electrode active material 31 and the second solid electrolyte 2 is avoided.
[0027] In an all-solid-state battery, the conductive material 4 on the negative electrode side is usually composed of a negative electrode active material 41 and a conductive material 42 other than the negative electrode active material. In an actual all-solid-state battery, the negative electrode material is generally composed of conductive materials such as a current collector and a large number of particles of a negative electrode active material, as well as particles of an ion conductive material (solid electrolyte) mixed to fill the spaces between the particles of the negative electrode active material. The conductive material 4 on the negative electrode side in FIG. 2 is a schematic diagram showing the positional relationship of the part of such a negative electrode material composed of a conductive material to the second solid electrolyte 2. The configuration of the conductive material 4 on the negative electrode side and the positional relationship between the conductive material 4 and the second solid electrolyte 2 can be the same as those of a known all-solid-state battery. Note that a third solid electrolyte may be placed between the second solid electrolyte 2 and the conductive material 4 on the negative electrode side as necessary.
[0028] 3 shows a schematic cross-sectional structure of one embodiment of an all-solid-state battery using particles of a positive electrode active material coated with the first solid electrolyte made of the ion-conductive lithium silicate-based mixed phase material according to the present invention and a second solid electrolyte mainly composed of a sulfide. In this figure, the cell structure is also drawn extremely simplified in order to explain the positional relationship of each member, and one particle of the positive electrode active material 31 is shown as a representative. The structure of the all-solid-state battery of this embodiment is basically the same as that of FIG. 2, except that the first solid electrolyte 1 is used as a coating material for the particles of the positive electrode active material 31.
[0029] 3, the first solid electrolyte 1 (lithium silicate-based mixed phase material) is interposed between the positive electrode active material 31 and the second solid electrolyte 2 (mainly composed of sulfide), thereby preventing direct contact between the positive electrode active material 31 and the second solid electrolyte 2. By making the thickness of the coating layer of the first solid electrolyte 1 (ionically conductive lithium silicate-based mixed phase material) sufficiently thin, a tunnel effect is exerted, and electrical conduction between the positive electrode active material 31 and the conductive material 32 other than the positive electrode active material is ensured even if they are not in direct contact with each other. EXAMPLES
[0030] [Example 1] (Dry grinding process) 4.0 g of lithium silicate Li4SiO4 powder (Toshima Seisakusho) and 17 zirconia balls with a diameter of 10 mm were placed in a grinding pot (zirconia, capacity 45 mL). This grinding pot was set in a planetary ball mill (Fritsch, Pulverisette-7), and dry grinding was performed under the conditions of a dew point temperature of 10°C and a rotation speed of 380 rpm in an air atmosphere. The dew point temperature was measured using a capacitance type dew point meter (Techno Measurement, TK-100). The contents were removed from the grinding pot every 4 hours, and the powder and zirconia balls were separated and collected. The collected powder was crushed in a mortar in an air atmosphere, and then returned to the grinding pot together with the 17 zirconia balls, and the grinding process was resumed under the above conditions. This mortar crushing was performed five times every 4 hours, and the dry grinding process was performed for a total of 24 hours. Thereafter, the contents were removed from the grinding pot, the powder and the zirconia balls were separated and collected, and the collected powder was crushed in a mortar in an air atmosphere. The powder thus obtained was used as a test material and subjected to the following measurements.
[0031] (X-ray diffraction measurement) For the powder sample as the test material, the X-ray diffraction pattern was measured by CuKα radiation using an X-ray diffractometer (Shimadzu Corporation, XRD-6100) under the following conditions: tube voltage: 40 kV, tube current: 30 mA, divergence slit: 1.0°, scattering slit: 1.0°, receiving slit: 0.3 mm, scan speed: 2.0° / min, step width: 0.02° / step, measurement time: 0.25 sec, measurement 2θ range: 15 to 55°. Peak search was performed using the analysis software attached to the device (XRD-6100) under the following conditions: smoothing processing: automatic, background processing: automatic, Ka1-a2 ratio: 50, peak search: automatic.
[0032] From the obtained X-ray diffraction pattern, the presence of four phases, Li4SiO4, Li2SiO3, Li2CO3, and LiOH·H2O, was confirmed. In other words, the test material in this example corresponds to a lithium silicate-based mixed phase material in which the above four phases exist. The diffraction peak intensities (cps values) for the specific planes (mentioned above) of these four phases are shown in Table 3 (the same applies to each of the following examples). When the diffraction peak intensity of the Li4SiO4 crystal (-1 1 0) plane is I0 and the diffraction peak intensity of the LiOH·H2O crystal (-3 3 1) plane is I1, the I1 / I0 ratio (hereinafter simply referred to as the "I1 / I0 ratio") was 0.56.
[0033] (composition analysis) 0.1g of the powder sample was weighed, and 10mL of pure water, 10mL of hydrochloric acid, and 5mL of nitric acid were added to it and dissolved by heating. The residue that could not be dissolved was collected with filter paper, and 1g of sodium potassium carbonate was added to the residue and alkali fusion was performed, after which 50mL of pure water and 5mL of hydrochloric acid were added and dissolved by heating. The solutions obtained by each of the above heating and dissolving were mixed, and the volume was adjusted using a 250mL measuring flask. After diluting 100 times, the concentration of the constituent elements of the solid electrolyte powder containing lithium and silicon in the diluted solution was measured using an inductively coupled plasma atomic emission spectrometer (ICP-AES, Agilent Technologies, CP-720). Tables 1 and 2 show the composition ratios of Li and Si based on the measurement results.
[0034] (Ionic conductivity measurement) A powder sample of 0.09 g of the test material was placed in a cylindrical container with a diameter of 10 mm, and pressed at 180 MPa with a press machine to obtain a green compact. The green compact was measured for ionic conductivity by AC impedance method at 25°C in an Ar atmosphere using a potentio / galvanostat (VersaSTAT4, manufactured by Prinston) in the range of 0.1 Hz to 1 MHz and an amplitude voltage of 100 mV. The resistance value of the sample was obtained from a Cole-Cole plot (complex impedance plane plot) of the measured values, and the ionic conductivity of the test material was calculated from the obtained resistance value. As a result, the ionic conductivity of the test material in this example was 1.1 × 10 -9S / cm, confirming that the solid electrolyte exhibited sufficient lithium ion conductivity. The results are shown in Table 1 (the same applies to the following Examples and Comparative Examples 1 to 4).
[0035] (Decomposition voltage measurement) Here, an all-solid-state electrochemical cell was fabricated in which the solid electrolyte (first solid electrolyte) of the test material and the sulfide-based solid electrolyte (second solid electrolyte) were adjacent to each other, and the decomposition voltage resulting from the oxidation reaction of the test material was determined in accordance with the evaluation method disclosed in Patent Document 1. Specifically, the experiment was carried out as follows.
[0036] An electrochemical cell having the layered structure shown in FIG. 4 was fabricated as follows. Argyrodite-type sulfide (Li6PS5Cl) was prepared as the second solid electrolyte. 57 mg of this sulfide was placed in an insulating outer cylinder (inner diameter 9.5 mm) made of an alumina tube and pressed at a pressure of 80 MPa to form a layer of the second solid electrolyte. Next, 20 mg of the powder sample was placed on the second solid electrolyte layer and pressed at a pressure of 80 MPa to form a first solid electrolyte layer. Next, 20 mg of a composite material obtained by mixing the powder of the test material and the powder of stainless steel (SUS316) in a mortar in a volume ratio of 50:50 was poured onto the first solid electrolyte layer and pressed at a pressure of 360 MPa to form a composite layer. Next, a 200 μm thick sheet of metallic In (indium), a 300 μm thick sheet of metallic Li, and a 200 μm thick sheet of metallic In were stacked in the above order underneath the second solid electrolyte layer (the opposite side to the first solid electrolyte), and pressed under a pressure of 80 MPa to form a counter electrode layer having an In / Li / In three-phase structure. Next, current collectors made of stainless steel (SUS316) plates were placed on the composite layer and under the counter electrode layer, respectively, and a current collecting lead was provided on each current collector.
[0037] The electrochemical cell prepared as described above was placed in a thermostatic chamber at 25°C, and the composite layer side was used as the working electrode, which is a high potential electrode, and the counter electrode layer side was used as the counter electrode, which is a low potential electrode. The voltage was swept from the open circuit voltage of the electrochemical cell to 6.0 V vs Li (synonymous with 5.4 V vs In-Li) at a sweep rate of 1 mV / s, and the fluctuation in current was measured. Hereinafter, unless otherwise specified, the potential value (V) represents the potential (V vs Li) based on Li. The potential (V vs Li) based on Li is the value obtained by adding 0.6 V to the potential (V vs In-Li) based on In-Li.
[0038] Although the solid electrolyte is originally an insulating material with respect to electrical conduction based on the movement of electrons, as shown in Patent Document 1, when the voltage applied to the working electrode in the above electrochemical cell is swept toward the high potential side, a small current flows at first, which is thought to be due to a non-Faraday reaction not involving the transfer of electrons, or a side reaction of adsorbed water or impurities. Then, when the first solid electrolyte undergoes an oxidation reaction and is altered (decomposed), a current associated with the oxidation reaction is observed. When the current starts to increase relative to the above-mentioned small current, which is the base current, it can be considered that the oxidation of the first solid electrolyte is occurring. According to the measurements of this example and the examples described later, in the region where the applied voltage exceeds 3.0 V in all examples, the current value changes flatly up to 4.0 V, and the change is also small, so here, the applied voltage at which a current value 1.5 times the current value at an applied voltage of 4.0 V is first observed is defined as the "decomposition voltage", and the high voltage application resistance characteristic is evaluated based on the decomposition voltage. The decomposition voltage of the test material in this example was 4.70 V. The results are shown in Table 2 (the same applies to each of the following Examples and Comparative Example 5). FIG. 5 shows an example of a potential-current curve measured using this electrochemical cell (the same applies to each of the following Examples and Comparative Example 5).
[0039] In addition, Patent Document 1 uniformly defines the oxidative decomposition voltage as the voltage at which a current of 3 μA flows (paragraph 0175). When the above decomposition voltage defined in this specification is calculated from the data shown in FIG. 3 of Patent Document 1, it is lower than the oxidative decomposition voltage (4.48 to 5.07 V calculated based on Li) of the examples shown in Table 1 of Patent Document 1. It can be said that the decomposition voltage defined in this specification adopts a stricter standard than Patent Document 1 in that the potential before a sudden increase in current value begins to occur is regarded as the decomposition voltage.
[0040] [Example 2] (Heat treatment process) A powder (ion-conductive lithium silicate-based mixed phase material) obtained by dry pulverization under the same conditions as in Example 1 was subjected to heat treatment in a box-type sintering furnace. The heat treatment conditions were an air atmosphere, a temperature increase rate of 5°C / min, and a holding time of 5 hours at 200°C. The powder obtained by this heat treatment was used as a test material and subjected to the same measurements as in Example 1.
[0041] From the X-ray diffraction pattern (Figure 1 above), it was confirmed that the test material in this example corresponds to a lithium silicate-based mixed phase material in which four phases, Li4SiO4, Li2SiO3, Li2CO3, and LiOH·H2O, exist. The I1 / I0 ratio was 0.33. In addition, the ionic conductivity of the test material in this example was 7.8×10 -10 S / cm, and it was confirmed that the solid electrolyte exhibited sufficient lithium ion conductivity. The decomposition voltage was 5.28 V. The decomposition voltage was improved compared to Example 1 by the heat treatment at 200°C.
[0042] [Example 3] A test material was obtained in the same manner as in Example 2, except that the temperature of the heat treatment was changed from 200° C. to 300° C. This test material was subjected to the same measurements as in Example 1.
[0043] From the X-ray diffraction pattern, it was confirmed that the test material in this example corresponds to a lithium silicate-based mixed phase material in which four phases, Li4SiO4, Li2SiO3, Li2CO3, and LiOH·H2O, exist. The I1 / I0 ratio was 0.13. In addition, the ionic conductivity of the test material in this example was 7.7×10 -11 It was confirmed that the solid electrolyte exhibited sufficient lithium ion conductivity, with a value of 0.1 S / cm. The decomposition voltage was 5.24 V. By increasing the heat treatment temperature to 300° C., the decomposition voltage was improved compared to Example 2, but the I1 / I0 ratio was decreased and the ionic conductivity was lower than that of Example 2.
[0044] [Example 4] In the dry grinding step, the total time of the grinding treatment was shortened to 5 hours, and the crushing treatment in a mortar was not performed during the dry grinding process, but the dry grinding was performed under the same conditions as in Example 1 to obtain a test material. This test material was subjected to the same measurements as in Example 1.
[0045] From the X-ray diffraction pattern, it was confirmed that the test material in this example corresponds to a lithium silicate-based mixed phase material in which four phases, Li4SiO4, Li2SiO3, Li2CO3, and LiOH·H2O, exist. The I1 / I0 ratio was 0.08. In addition, the ionic conductivity of the test material in this example was 3.1×10 -11 It was confirmed that the solid electrolyte exhibited sufficient lithium ion conductivity, with a decomposition voltage of more than 6.0 V. By shortening the grinding time, a lithium silicate-based mixed phase material exhibiting a high decomposition voltage was obtained, but the I1 / I0 ratio was low and the ionic conductivity was lower than in other examples.
[0046] [Comparative Example 1] A test material was obtained in the same manner as in Example 2, except that the heat treatment temperature was changed from 200° C. to 650° C. For this test material, X-ray diffraction measurement and ion conductivity measurement were performed in the same manner as in Example 1.
[0047] Figure 6 shows the X-ray diffraction pattern of the test material obtained in this example. In this X-ray diffraction pattern, the diffraction peak of the Li4SiO4 phase was observed, and the presence of other phases could not be confirmed. For reference, Figure 7 shows the X-ray diffraction pattern of the Li4SiO4 powder (before being subjected to dry grinding) used as the raw material. Comparing Figures 6 and 7, it is considered that the test material in this example is a single phase Li4SiO4. The ionic conductivity of this test material was 1.0 × 10 -11 In other words, if the heat treatment temperature is too high, the mixed phase structure of the four phases described above collapses and the ionic conductivity is lost.
[0048] [Comparative Example 2] Except for changing the raw material from 4.0 g of Li4SiO4 powder to 4.0 g of lithium metasilicate Li2SiO3 powder (manufactured by Wako Pure Chemical Industries, Ltd.), dry grinding (total grinding time: 24 hours) and heat treatment (200°C for 5 hours) were performed under the same conditions as in Example 2 to obtain a test material. X-ray diffraction measurement and ionic conductivity measurement were performed on this test material in the same manner as in Example 1.
[0049] The X-ray diffraction pattern showed that the material in this example was Li2SiO3. The ionic conductivity of this material was 1.0×10 -11 In other words, even if the lithium metasilicate Li2SiO3 was subjected to the dry grinding and heat treatment under the above conditions, an ion-conductive lithium silicate-based mixed phase material was not obtained.
[0050] [Comparative Example 3] Dry grinding (total grinding time: 5 hours) was performed under the same conditions as in Example 4, except that the atmosphere in the dry grinding step was changed from an air atmosphere with a dew point temperature of 10° C. to an air atmosphere with a dew point temperature of −60° C., to obtain a test material. X-ray diffraction measurement and ion conductivity measurement were performed on this test material in the same manner as in Example 1.
[0051] The X-ray diffraction pattern showed that the test material in this example was Li4SiO4. The ionic conductivity of this test material was 1.0×10 -11In other words, if there is not enough moisture in the atmosphere when the lithium silicate Li4SiO4 is dry-milled, it is difficult to synthesize an ion-conductive lithium silicate-based mixed-phase material having the above four phases.
[0052] [Comparative Example 4] Powder (still Li4SiO4) obtained by dry pulverization (dew point temperature: -60°C) similar to that in Comparative Example 3 was subjected to a heat treatment (200°C for 5 hours) similar to that in Example 2. X-ray diffraction measurement and ionic conductivity measurement were performed in the same manner as in Example 1 using the powder obtained by this heat treatment as a test material.
[0053] The X-ray diffraction pattern showed that the test material in this example was Li4SiO4. The ionic conductivity of this test material was 1.0×10 -11 It was less than S / cm.
[0054] [Comparative Example 5] Powder of lithium niobate LiNbO3, which has been used conventionally as a protective material for positive electrode active materials, was synthesized by the liquid phase method described below. A hydrogen peroxide solution was prepared by adding 7.7 g of hydrogen peroxide solution with a concentration of 35 mass% to 19.6 g of pure water. After adding 4.4 g of niobic acid (Nb2O5·nH2O) with a Nb2O5 content of 58.0% to this hydrogen peroxide solution, the liquid temperature was maintained at 20-30°C, 3.5 g of ammonia water with a concentration of 28 mass% was added, and the mixture was thoroughly stirred in an air atmosphere to obtain a transparent solution. Next, 0.9 g of lithium hydroxide monohydrate (LiOH·H2O) was added to this solution in a nitrogen atmosphere to obtain a transparent aqueous solution containing lithium and peroxo complexes, and the liquid was heated on a hot plate at 100°C in a nitrogen atmosphere to evaporate and dry. The dried and solidified product was then subjected to a heat treatment at 200°C for 12 hours to obtain amorphous LiNbO3 powder. The decomposition voltage was measured in the same manner as in Example 1 using this heat-treated powder as a test material.
[0055] The decomposition voltage of the conventional material, lithium niobate LiNbO3, was 4.36V. The above results are summarized in Tables 1 and 2. Table 3 shows the diffraction peak intensities for the specific planes (mentioned above) of the four phases observed in the X-ray diffraction patterns of Examples 1 to 4.
[0056] [Table 1]
[0057] [Table 2]
[0058] [Table 3]
[0059] The lithium silicate-based mixed phase materials obtained in each example have excellent high voltage application resistance (decomposition voltage) when adjacent to a sulfide-based solid electrolyte, and are therefore useful as protective materials for positive electrode active materials, and can contribute to improving the charging voltage of all-solid-state batteries. [Explanation of symbols]
[0060] 1. The first solid electrolyte 2. Second solid electrolyte 3. Positive electrode conductive material 4. Conductive material on the negative electrode 31 Cathode active material 32 Conductive materials other than positive electrode active materials 41 Negative electrode active material 42 Conductive materials other than negative electrode active materials
Claims
1. In the X-ray diffraction pattern using CuKα radiation, Li 4 SiO 4 , Li 2 SiO 3 , Li 2 CO 3 , LiOH.H 2 Ion-conducting lithium silicate-based mixed phase material in which the presence of four phases of O is observed.
2. 2. The lithium silicate-based mixed phase material according to claim 1, wherein the Li / Si molar ratio is in the range of 3.5 to 4.
5.
3. Li in the X-ray diffraction pattern 4 SiO 4 The diffraction peak intensity of the crystal (-1 1 0) plane is I 0 , LiOH.H 2 The diffraction peak intensity of the (-3 3 1) plane of the O crystal is I 1 Then, I 1 / I 0 2. The lithium silicate based mixed phase material of claim 1, wherein the ratio is 0.05 or more.
4. Li in the X-ray diffraction pattern 4 SiO 4 The diffraction peak intensity of the crystal (-1 1 0) plane is I 0 , LiOH.H 2 The diffraction peak intensity of the (-3 3 1) plane of the O crystal is I 1 Then, I 1 / I 0 2. The lithium silicate based mixed phase material of claim 1, wherein the ratio is 0.25 or greater.
5. 13. An all-solid-state battery comprising the ion-conductive lithium silicate-based mixed phase material according to claim 1 between a conductive material on a positive electrode side and a conductive material on a negative electrode side.
6. 13. An all-solid-state battery comprising the ion-conductive lithium silicate-based mixed phase material according to claim 1 and a solid electrolyte containing a sulfide as a main component between a positive electrode conductive material and a negative electrode conductive material.
7. 13. An all-solid-state battery comprising a positive electrode active material, a first solid electrolyte made of the ion-conductive lithium silicate-based mixed phase material according to claim 1, a second solid electrolyte containing a sulfide as a main component, and a negative electrode active material, the all-solid-state battery having a structure in which the first solid electrolyte is interposed between the positive electrode active material and the second solid electrolyte, thereby avoiding direct contact between the positive electrode active material and the second solid electrolyte.
8. 13. An all-solid-state battery comprising: particles of a positive electrode active material coated with a first solid electrolyte comprising the ion-conductive lithium silicate-based mixed phase material according to claim 1; a second solid electrolyte containing a sulfide as a main component; and a negative electrode active material.
9. Lithium Silicate Li 4 SiO 4 2. The method for producing an ion-conductive lithium silicate-based mixed phase material according to claim 1, further comprising a step of dry-grinding the above in an air atmosphere having a dew point temperature of -30°C or higher.
10. Lithium Silicate Li 4 SiO 4 in an air atmosphere having a dew point temperature of −30° C. or higher to produce a lithium silicate-based mixed phase substance; Heat-treating the lithium silicate-based mixed phase material in air at 100° C. or more and 500° C. or less; 2. The method for producing an ion-conducting lithium silicate-based mixed phase material according to claim 1, comprising:
Citation Information
Patent Citations
Method for producing lithium silicate compound
WO2010089931A1
Positive electrode material, and battery
WO2020174868A1